2010
DOI: 10.1155/2010/262601
|View full text |Cite
|
Sign up to set email alerts
|

A New Validated RP‐ HPLC Method for the Determination of Nevirapine in Human Plasma

Abstract: A rapid, selective and sensitive high performance liquid chromatographic method for the estimation of nevirapine in human plasma has been developed. Chromatography was carried out on a Hypersil BDS C 18 column using a mixture of ammonium acetate buffer (pH 4.0 + 0.05) and acetonitrile (85:15 v/v) as the mobile phase. The eluents were monitored for the drug by UV detection at 254 nm. Oxcarbazepine was used as an internal standard for this study. The retention times for nevirapine and oxcarbazepine were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…As selectivity of mass detectors is less prone to interference compared to UV and other non-speci ic detectors, UPLC-MS/MS method was selected for the determination of both impurities. HPLC method is available for the determination of penciclovir in plasma sample (Kumar et al, 2010). Bioequivalence study of penciclovir is reported in the literature (Pan et al, 2008).…”
Section: Figure 1: Structures Of Penciclovir and Two Genotoxic Impurimentioning
confidence: 99%
“…As selectivity of mass detectors is less prone to interference compared to UV and other non-speci ic detectors, UPLC-MS/MS method was selected for the determination of both impurities. HPLC method is available for the determination of penciclovir in plasma sample (Kumar et al, 2010). Bioequivalence study of penciclovir is reported in the literature (Pan et al, 2008).…”
Section: Figure 1: Structures Of Penciclovir and Two Genotoxic Impurimentioning
confidence: 99%
“…[3][4][5] Literature review reveals that HPLC, [6][7][8][9][10][11] UV [12][13][14] spectrophotometric and HPTLC [15][16][17][18][19][20] methods have been reported for quantification of TEL in pharmaceutical dosage form. Chlorthalidone is chemically a 2-Chloro-5-(1-hydroxy-3-oxo-1-isoindolinyl) benzene sulfona-mide is thiazidelike diuretic.…”
Section: British Pharmacopoeia (Bp) and Us Pharmacopoeia (Usp) It mentioning
confidence: 99%
“…It is official in BP [2], USP [3], EP [4] and IP [5]. A literature survey revealed that many methods are reported for the determination of TEL by spectrophotometry [6,7], HPLC [8,9], LC-MS/MS [10,11], and HPTLC [12,13].…”
Section: Introductionmentioning
confidence: 99%